2020
DOI: 10.4995/eurocall.2020.12974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamification on students’ motivation and learning achievement in Second Language Acquisition within higher education: a literature review 2011-2019

Abstract: <h4>This paper focuses on a fairly new motivational technique, the so-called Gamification, which consists of introducing game mechanics in non-game environments to promote motivation and engagement. By the turn of the 21rst century, Gamification took off in the business field and soon after became an attractive concept for researchers and professionals in education as it appears to be an increasingly popular method to motivate learners. Nevertheless, it is still a nascent field in terms of empirical evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…Prior research has supported the effectiveness of using gamification in learning environments, especially for promoting motivation and engagement (Boudadi & Gutiérrez-Colón, 2020;Dong et al, 2012;Pesare et al, 2016). However, the present study did not demonstrate any benefits of using game design elements in non-game contexts.…”
Section: The Application Of Game Design Elementscontrasting
confidence: 80%
“…Prior research has supported the effectiveness of using gamification in learning environments, especially for promoting motivation and engagement (Boudadi & Gutiérrez-Colón, 2020;Dong et al, 2012;Pesare et al, 2016). However, the present study did not demonstrate any benefits of using game design elements in non-game contexts.…”
Section: The Application Of Game Design Elementscontrasting
confidence: 80%
“…Repeated quizzes with the use of gamification may therefore result in a lasting interest (Topîrceanu, 2017). The gamification literature, more broadly, would benefit from such an approach, since most of the previous experiments last just one or very few sessions (Boudadi & Gutiérrez-Colón, 2020;Sun and Hsieh, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One of the first reviews was conducted by Subhash and Cudney (2018) and supported several benefits of gamification such as improved students' performance, motivation, and learning perception. Another review study was conducted in the English language field by Boudadi and Gutierrez-Colon (2020) and found that gamification enhanced students' motivation and their learning engagement. Another study in the social environment field conducted by Brito and Mena (2020) indicated that gamification enhanced students' engagement and motivation levels.…”
Section: Contemporary Educational Technology 2023mentioning
confidence: 99%
“…Studies dedicated to gamification in general and in particular in science are still lacking. Furthermore, of those conducted, some indicated mixed findings as to the intervention's effectiveness (Boudadi & Gutierrez-Colon, 2020;Kalogiannakis et al, 2021). Recent studies on gamification to individual discipline are also still insufficient and further research is needed.…”
Section: Contemporary Educational Technology 2023mentioning
confidence: 99%